Economic Recession and the Long Term Risk of Psychiatric Disorders and Alcohol Related Diseases—A Cohort Study From Eastern Finland - Jarroch, Rand; Tajik, Behnam; Tuomainen, Tomi-Pekka; Kauhanen, Jussi (Frontiers in Psychiatry, 2022)
Background: Long-term development of psychiatric disorders and alcohol-related diseases after economic recessions is insufficiently studied. We investigated the overall impact of the economic recession between 1991−1994 in Finland on the long-term incidence of psychiatric and alcohol-related diseases. Methods: A population-based sample of 1,774 women and men aged 53−73 years were examined between 1998−2001 from the Kuopio Ischemic Heart Disease Risk Factor Study (KIHD). Participants completed comprehensive questionnaires on the possible impact of the 1990s recession in Finland on their lives. They were followed-up until 2018. Cox proportional hazards regression was used to estimate hazard ratios (HR) of new incident psychiatric and alcohol-related disorders during the 20-years follow-up after linkage to the National Hospital Registry. Logistic regression was used to estimate odds ratios (OR) of psychiatric disorders at baseline. Results: At baseline, 93 participants had psychiatric disorders. During 20-years follow-up, 138 new psychiatric disorders and 45 alcohol-related diseases were developed. The covariate-adjusted risk of psychiatric disorders was over twice higher among men who experienced recession-induced hardships compared to those who did not (HR=2.20, 95%CI=1.04−4.70, p=0.04). The risk of alcohol-related diseases was more than four times higher among men with hardships (HR=4.44, 95%CI=1.04−18.90, p=0.04). No such associations were observed among women. No association was observed between recession-induced hardships and having psychiatric disorders at baseline in both genders (multivariate-adjusted p=0.63 for women, multivariate-adjusted p=0.36 for men). Conclusion: Long-term risk of psychiatric disorders and alcohol-related diseases was increased after the 1990s economic recession in Finland, but only among middle-age and older men.